Swallowing patterns after adenotonsillectomy in children - de Oliveira Branco, Anete Antunes [UNESP]; de Castro Corrêa, Camila [UNESP]; de Souza Neves, Daniela [UNESP]; Huehara, Tais [UNESP]; Theresa Weber, Silke Anna [UNESP] (Wiley, 2019)
Importance: Hypertrophy of the pharyngeal and palatine tonsils can interfere with breathing, physical and cognitive development, and quality of life, including sleep quality. There are important relationships between the muscles of the airways, the anatomy, and the pattern of breathing and swallowing. Objective: The aims of the present study were to evaluate the swallowing process in children after adenotonsillectomy undertaken to treat obstructive breathing disorders. Methods: Subjects were 85 children or adolescents who underwent adenotonsillectomy in a reference hospital between 2003 and 2007. For the clinical evaluation of swallowing, the protocol of orofacial myofunctional evaluation with scores (OMES) was used, videofluoroscopy of deglutition was performed, and the Dysphagia Outcome and Severity Scale (DOSS) and Classification for Severity of Dysphagia to Videofluoroscopy Scale were applied for analysis. Results: Out of the 85 evaluated children, 43 were male (50.59%), the average age at evaluation was 12.11 years, the average age at the time of surgery was 6.73 years, and post-surgery time was 3.00–8.00 years. In the clinical evaluation of swallowing, half the sample (50.59%) recorded the poorest score for lip and tongue behavior. A score of 1 was observed in 67.06% of subjects for other behaviors, and in 15.30% of subjects for efficiency of swallowing. Videofluoroscopic analysis demonstrated that the most frequent swallowing alterations were labial sealing (50.59%), residue in vallecula (51.76%), and use of compensatory maneuvers (61.18%). Analysis of DOSS showed that normal swallowing was attributed to 48.31% of subjects at level 7, 44.95% at level 6, and 6.74% at level 5. For the Classification for Severity of Dysphagia to Videofluoroscopy, 75.28% were classified as having mild dysphagia. Interpretation: Alterations in the dynamics of swallowing are common in children who have undergone surgery of the tonsils, even at late follow-up.
Keywords: Adenoids; Child; Deglutition; Deglutition disorders; Palatine tonsil